2012
DOI: 10.1038/modpathol.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular heterogeneity of TFE3 activation in renal cell carcinomas

Abstract: Renal cell carcinomas associated with Xp11.2 translocations have recently been identified as a distinct biological entity. The translocation results in the fusion of the transcription factor TFE3 to one of several different fusion partners including PRCC, PSF, NONO, ASPL or CTLC with consecutive overexpression of the chimeric protein. As the true frequency of these neoplasms as well as the biological properties of TFE3 activation in renal cell carcinomas are largely unknown, we have examined TFE3 expression as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
72
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 22 publications
7
72
3
Order By: Relevance
“…4,6,9,14,47 Xp11.2 renal cell carcinoma can also be misdiagnosed as papillary renal cell carcinoma when cytoplasmic clearing is present because of degeneration associated with hemosiderin deposition as well as when the Xp11.2 renal cell carcinoma has prominent eosinophilic cytoplasm that can mimic type 2 papillary renal cell carcinoma. 3,4,6,9,14 IHC is a potential screening tool for Xp11.2 renal cell carcinoma but does not have sufficient sensitivity or specificity to establish TFE3 rearrangement; true TFE3 disruption was confirmed by FISH only in four of the nine (44%) well-characterized renal cell carcinoma tumors that had moderate-to-strong nuclear TFE3 immunoreactivity in each of two recent studies, 28,29 and fixation-related artifacts have been reported, such as an affinity for the edges as well as variability in antibody batch performance. 30,48,49 Similar findings occurred for alveolar soft part sarcoma where only 22 of the 24 cases of TFE3/ASPSCR1 confirmed by FISH were positive by IHC and, importantly, TFE3 immunoreactivity was also noted in two of five non-alveolar soft part sarcoma neoplasms (granular cell tumors) that were negative by FISH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,9,14,47 Xp11.2 renal cell carcinoma can also be misdiagnosed as papillary renal cell carcinoma when cytoplasmic clearing is present because of degeneration associated with hemosiderin deposition as well as when the Xp11.2 renal cell carcinoma has prominent eosinophilic cytoplasm that can mimic type 2 papillary renal cell carcinoma. 3,4,6,9,14 IHC is a potential screening tool for Xp11.2 renal cell carcinoma but does not have sufficient sensitivity or specificity to establish TFE3 rearrangement; true TFE3 disruption was confirmed by FISH only in four of the nine (44%) well-characterized renal cell carcinoma tumors that had moderate-to-strong nuclear TFE3 immunoreactivity in each of two recent studies, 28,29 and fixation-related artifacts have been reported, such as an affinity for the edges as well as variability in antibody batch performance. 30,48,49 Similar findings occurred for alveolar soft part sarcoma where only 22 of the 24 cases of TFE3/ASPSCR1 confirmed by FISH were positive by IHC and, importantly, TFE3 immunoreactivity was also noted in two of five non-alveolar soft part sarcoma neoplasms (granular cell tumors) that were negative by FISH.…”
Section: Discussionmentioning
confidence: 99%
“…To address diagnostically challenging cases of alveolar soft part sarcoma and Xp11.2 renal cell carcinoma, consideration of clinical presentation and histopathologic features has historically been supplemented by immunohistochemistry (IHC) for TFE3 protein; however, the antibody is limited in sensitivity and specificity, [28][29][30][31][32] which may be influenced by the method employed. 33 A genetic approach is therefore required to confirm TFE3 rearrangement.…”
mentioning
confidence: 99%
“…Finally, a strong nuclear labeling for TFE3 is the most distinctive features of Xp11.2 RCCs, reflecting an overexpression of the translocation-associated chimeric protein [1]. However, recent studies indicate that TFE3 immunostaining can show false-positive, false-negative and equivocal results, which has resulted in a growing recognition that the diagnosis of Xp11.2 RCCs needs to be verified using molecular techniques [15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…However, excessive antigen retrieval can lead to false-positive results because native TFE is ubiquitously distributed (nonneoplastic tissue is a convenient internal negative control), and a negative TFE3 IHC cannot completely exclude a diagnosis of Xp11.2 translocation RCC. 46 Interestingly, a recent study 47 adds more complexity to this picture. Macher-Goeppinger et al 47 showed that TFE3 activation is not limited to Xp11.2 translocation RCC but may also be observed in a subset of nontranslocation RCCs associated with aggressive clinical behavior and poor survival.…”
Section: Translocation Rccmentioning
confidence: 99%
“…46 Interestingly, a recent study 47 adds more complexity to this picture. Macher-Goeppinger et al 47 showed that TFE3 activation is not limited to Xp11.2 translocation RCC but may also be observed in a subset of nontranslocation RCCs associated with aggressive clinical behavior and poor survival. Hence, IHC by TFE3 will give us most, but not all, of the answers.…”
Section: Translocation Rccmentioning
confidence: 99%